When Medical English as a Lingua Franca becomes Medical English for Research and Publication Purposes: A Metacognitive Approach to Student Dissertation Revision - Nikitina, Jekaterina (Status Quaestionis, 2024)
Medical English as a Lingua Franca is increasingly used around the world, yet the context of university education, and specifically, the publication of final dissertations, remains impervious to the idea of contact languages and requires native-like quality, thus creating demand for proofreading/revision services. This study overviews results of an applied-purpose collaborative interuniversity project, wherein final dissertations by intermediate-level English L2 students pursuing a degree in health sciences were revised by advanced-level English L2 students with a linguistic specialism, applying a metacognitive revision model. The theoretical-methodological framework relies on an eclectic combination of insights from English as a Lingua Franca, learner corpora and crosslinguistic influence, English for research and publication purposes and proofreading/revision services. The findings reflect on possible curricular interventions, both for healthcare students and for foreign language students, to enhance their specific skillset in the spirit of interprofessional communication.